Perceived Caretaker Malevolence During Childhood Reported by Borderline Patients and Personality-Disordered Comparison Subjects: Description and Prediction - Ridolfi, Maria E; Temer, Christina M; Fraser, Emily K; Frankenburg, Frances R; Zanarini, Mary C (Journal of personality disorders, 2020)
This study has two purposes. The first is to assess the rates of childhood malevolence by caretakers reported by a well-defined sample of inpatients with borderline personality disorder (BPD) and comparison subjects with other personality disorders. The second purpose is to determine the relationship between reported malevolence of caretakers and possible risk factors for this experience. Two reliable interviews were administered to 290 borderline inpatients and 72 personality-disordered comparison subjects to address these aims. Malevolence was reported by a significantly higher percentage of borderline patients than comparison subjects (58% vs. 33%). In multivariate analyses, severity of other forms of abuse, severity of neglect, and a family history of a dramatic cluster personality disorder were found to significantly predict perceived malevolence. Taken together, the results of this study suggest that experiencing malevolence is common and distinguishing for BPD, and that the risk factors for reported childhood malevolence are multifactorial in nature.